2022
DOI: 10.3390/cancers14246251
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Spinal Meningiomas Epidemiology, Tumor Characteristics and Non-Surgical Treatment Options: A Systematic Review and Pooled Analysis (Part 1)

Abstract: Background: Spinal meningiomas are the most common primary intradural spinal tumors. Although they are a separate entity, a large portion of the knowledge on spinal meningiomas is based on findings in intracranial meningiomas. Therefore, a comprehensive review of all the literature on spinal meningiomas was performed. Methods: Electronic databases were searched for all studies on spinal meningiomas dating from 2000 and onward. Findings of matching studies were pooled to strengthen the current body of evidence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 91 publications
(229 reference statements)
1
46
0
Order By: Relevance
“…PSAM is extremely understudied due to its rarity ( Table 2 ). Spinal meningioma is generally considered to have female predilection and the corresponding male to female ratio ranges from 1:1.5 to 1:14.5 ( 2 , 19 , 20 ). However, the numbers of male and female patients are even in our small sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSAM is extremely understudied due to its rarity ( Table 2 ). Spinal meningioma is generally considered to have female predilection and the corresponding male to female ratio ranges from 1:1.5 to 1:14.5 ( 2 , 19 , 20 ). However, the numbers of male and female patients are even in our small sample.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, spinal meningiomas most frequently occur in older patients ( 22 ). A systematic review concluded the average age of spinal meningiomas was 62.6 years old after adjusting the sample size of various studies ( 20 ). The median age of our patients was 25 (range, 13–46) years, while the median age of literature cases was 55 (range, 47–68) years ( 8 , 9 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis will only be performed for research questions where rigorous, homogeneous and sufficient data are available. A similar methodology has been described in several of our previous works 44–47…”
Section: Methods and Analysismentioning
confidence: 99%
“…Spinal meningiomas remain a surgical disease due to a limited number of studies using non-surgical therapies. 78 Though pharmacotherapy is often discussed as a treatment for recurrent meningiomas, or those refractory to all surgical and RT modalities, 79 its role remains poorly defined with no reliable evidence on which to base recommendations for routine clinical use. 50 Many types of systemic therapy for solid CNS tumors have been studied for use in meningioma.…”
Section: Treatment Modalitiesmentioning
confidence: 99%